Resposta pulpar em molares de camundongos após capeamento pulpar direto com novas formulações de biovidros - Hebertt Gonzaga dos Santos Chaves (2022)
When the dental pulp is exposed to the oral environment, a wound is created in the pulp tissue, whose treatment must be immediately instituted by cleaning and disinfecting the area, followed by pulp coverage with a bioactive material. The objective of this study was to evaluate the response of pulp tissue to bioglasses F18 and F18 doped with cobalt (F18Co) compared to calcium hydroxide (CH), after direct pulp capping. For that, 48 male Balb/C mice (8 weeks old) had their right and left maxillary first molars randomly divided into groups: F18, F18Co, CH and control. The molars of the experimental groups had the coronal pulps exposed and received the materials, and were sealed with glass ionomer. The control group received no intervention. After 7 and 15 days, the animals (n = 6) were euthanized and the specimens processed to evaluate the inflammatory process and tissue disorganization, using Hematoxylin-Eosin staining, and cytokine expression, using the PCR technique in real time, where interleukins (IL)-1β, IL-6 and IL-10 were evaluated. At 7 and 15 days, there was mild to moderate inflammation in the CH group, and mainly moderate to severe in F18 and F18Co, however, a significant difference was observed only between the control group, without inflammation, and the F18 and F18Co groups (P < 0.05). Regarding tissue disorganization, at 7 days, moderate disorganization was observed for the CH and for most specimens F18 and F18Co; at 15 days, there was mild to moderate disorganization for CH and moderate to severe for F18 and F18Co; the difference was observed between the control and F18 and F18Co groups (P < 0.05), in both analysis periods. Tertiary dentin formation was observed only at 15 days in all experimental groups, however, more intensely in the CH group. At 7 days, there was no significant difference between the groups in terms of IL-6 and IL-10 expressions. Regarding the expression of IL-1β, was possible to observe a significant increase in the CH and F18 groups. At 15 days, there was greater expression of IL-6 in groups F18 and F18Co compared to control; a significant increase in IL-1β expression was observed in this period in the F18 and F18Co groups compared to the CH and control groups. There was no significant expression of IL-10 in the different groups. It is concluded that the bioglasses F18 and F18Co may have a lower performance than CH when used in direct contact with the pulp tissue.